Molecular Typing of Human Brucella melitensis Isolated from Patients in Erbil, Iraq - Amin, Bushra K.; Hassan, Khulod I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
Brucellosis is a reemerging infectious zoonotic disease of worldwide importance. In the Kurdistan Region of Iraq, it is a widely spread disease and remains a challenging health problem. This disease is mainly caused by Brucella melitensis, in human. For confirmation of these isolates, a study was performed, by isolation and molecular typing of Brucella Spp. from human patients in Rizgari Hospital at Erbil city (Iraq), between March 2014 and November 2016. One hundred sixty seven samples of blood collected from patients suspected for brucellosis, one hundred twenty one samples from these were recorded as genus of Brucella, using biochemical test and confirmed by applying polymerase chain reaction (PCR), using genus specific primer for omp31 gene which was specific for B. melitensis. These results support using molecular method that based on PCR as diagnostic test for the control of brucellosis in Erbil. Further studies are needed from different geographical areas of the country with different level of endemicity to plan and execute control strategies against human brucellosis.